Welch powell algoritma aplication to identify the conflict of lesson timetable (case study: informatics engineering, stikom yos sudarso Purwokerto) - Diandra Chika Fransisca; Safar Dwi Kurniawan (Indonesian Institute For Counseling, Education and Therapy, 2020)
The lecture timetable is a requirement which done each semester by an academic system department in a university. The academic system department faces lecture schedule conflict while they are making it. Welsh Powell algorithm is one of graph theory which can be a solution for the academic system department in a university to avoid the conflict. Accordingly, the purpose of the research is to apply the Welch Powell algorithm for detecting lecture schedule conflict in Informatics Engineering major in STIKOM Yos Sudarso in even semester. The researcher uses two stages of the research method in this study: to collect the data and to implement the model. This research collects the needed data from Informatics Engineering students who take the lecture in even semester. While in the implementation, the researcher collects the model data afterward processed with the Welch Powell algorithm. The conclusion of this research is the Welch Powell algorithm is effective to avoid the conflict of the lesson timetable. The algorithm produces chromatic number 8. It means using the Welch Powell algorithm has 8 conditions course scheduling which can be set so that the conflict does not happen.